Attracting and Retaining International Talent in North Karelia - Villanen, Riku (2023)
As companies worldwide are experiencing shortages in skilled workforce, the race for talent has intensified both domestically and internationally. This thesis aims to identify and explore how companies in North Karelia can attract, recruit and retain international talent. The theoretical framework identifies the state of North Karelian labor markets, challenges international employees may face while looking for employment in Finland and how companies can attract and retain talent through the talent attraction management model. Qualitative research methods were chosen to gain a deeper understanding of how organizations could attract and retain talent in the region more effectively. This research was carried out by interviewing three different local companies. The interviews are analyzed, and suggestions for attraction and retaining factors of international talent in North Karelia are given.